In-Depth Evaluation of a Case of Presumed Myocarditis After the Second Dose of COVID-19 mRNA Vaccine - Muthukumar, Alagarraju; Narasimhan, Madhusudhanan; Li, Quan-Zhen; Mahimainathan, Lenin; Hitto, Imran; Fuda, Franklin; Batra, Kiran; Jiang, Xuan; Zhu, Chengsong; Schoggins, John; Cutrell, James B.; Croft, Carol L.; et al. (Circulation (New York, N.Y.), 2021)
Supplemental Digital Content is available in the text.